Silent Struggles: Depression and Its Link to Suicide Attempts in Emerging Adulthood - Purba, Novia Sri Parindu; Kastanya, Lidia; Sherly, Sherly; Tju, Meriana; Christabel, Valencia (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Depression is one of the leading causes of morbidity and mortality worldwide, including in Indonesia. It is a mood disorder characterized by persistent feelings of sadness, loss of interest or pleasure in daily activities, and various physical and cognitive symptoms that impair an individual's functioning. Early adulthood is a vulnerable developmental period, as individuals often face significant social, academic, and professional pressures that, if unmanaged, may lead to complex psychological issues. When untreated, depression during this stage can escalate into more serious conditions, such as suicidal ideation or attempts. The emergence of suicidal ideation is often driven by psychological distress, both emotional and physical. Contributing factors include limited access to psychological support, social stigma surrounding mental health, and a lack of awareness about the symptoms of depression. These issues often lead to many cases of depression and suicidal ideation going undetected or untreated. However, previous studies have shown that attachment to life can act as a protective factor, reducing the risk of suicide. This study aims to explore the subjective experiences of young adults in Indonesia who are living with depression and have had suicidal ideation or attempts. Using a qualitative phenomenological approach, data were collected through in-depth interviews with participants aged 20–30 who met the criteria for depression and had a history of suicidal ideation or attempts. Thematic analysis was employed to identify core themes related to their emotional experiences, coping mechanisms, and meaning-making processes. This research is expected to provide a deeper understanding of the lived experiences of depression and suicidality in early adulthood within the Indonesian cultural context, and to contribute to more culturally sensitive mental health interventions.